In Vitro Activities of Three Nonfluorinated Quinolones against Representative Bacterial Isolates - Barry, Arthur L. (American Society for Microbiology, 2001)
In vitro susceptibility tests were performed to document the inhibitory activities of three nonfluorinated quinolone (NFQ) compounds (PGE 9262932, PGE 9509924, and PGE 4175997) compared to those of ciprofloxacin, levofloxacin, and trovafloxacin against 3,030 bacterial isolates. The spectra of the NFQ agents included most gram-positive species as well as quinolone-susceptible Enterobacteriaceae. Ciprofloxacin-resistant, methicillin-resistant Staphylococcus aureus strains were inhibited by the NFQ series at ≤1.0 μg/ml. The NFQ compounds were not very active against Pseudomonas aeruginosa and most other nonfermentative gram-negative bacilli. Against other species, the potency of the NFQ agents was similar to that of trovafloxacin. Continued investigation of the NFQ compounds seems to be warranted.